Attack intensity of sucking pods insect pest (Riptortuslinearis) in different age of soybean under drought stress conditions. Issue 1 (March 2021) - Sarjan, M; Fathiyani, B D S; Yassi, A
Abstract: The aims of this investigation are to determine the level of Attack Intensity of Sucking pods Insect Pest in a different age of the soybean plant under drought stress conditions. This Investigation has been carried out in the greenhouse of the Faculty of Agriculture, University of Mataram . The experimental method was used in this investigation in the greenhouse of the Faculty of Agriculture University of Mataram. The Completely Randomized Design (CRD) factorial was used, which were treatments consisting of two factors: Age Factors of Investment Pest (A) consist of before flowering (A1), the time of flowering (A2), and when the pods are filling (A3). While Factor of gk/mdVarieties (V) consists of a variety of Anjasmoro (V1), Grobogan (V2), and Kaba (V3). Parameters measured were: 1) Age of flowering; 2) Plants High; 3) Water Needs; 4) The attack intensity of pests; 5) The number of pods; 6) The number of pods filled; 7) The number of empty pods because of pests; 8) Number of empty pods because of drought; 9) The number of seeds per plant; 10) Weight of 100 seeds; 11) Seeds results per plant; 12).The percentage of yield loss. Data were analyzed by using Analysis Of Variance (ANOVA) at 5 (five) percent significance level. Results showed that: 1) The highest sensitivity was found when pests were invested in soybean pod filling; 2) The pests release time causing the different level attack intensity and causing the different levels of yield loss. The highest yield lost was found when the pests release during pods filling, followed by pest release during flowering, and the lowest yield lost was when its release/invests before flowering.